Development of a 2D Animated Media Based on Greek Mythology, “The Love Tragedy,” to Enhance Perception of Love and Loss - ชมภูหอม, สุดารัตน์; สีใส, ศิขรินธร; ดีเจริญชิตพงศ์, จิรวิญญ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The research on 2D animation media, specifically vector animation, titled "The Myth of Love between Adonis and Aphrodite," was conducted to convey a story from Greek mythology. It depicts the tragic love that led to the creation of the red rose a symbol of beautiful love that comes at the cost of pain and loss. Through a production process involving character design, background design, and lighting and color direction tailored to the story's emotional tone, the animation serves as a medium to disseminate classic literature while embedding a moral lesson on heedlessness. The objectives of this research were: 1) to study and design an animation about the myth of love between Adonis and Aphrodite, emphasizing a new interpretation through symbolism; 2) to communicate the meaning of the red rose as a symbol of love born from loss and blood, enabling the audience to understand its profound origin beyond superficial beauty; and 3) to make the audience realize the value of love and the importance of heeding warnings through the characters' tragedy, which reflects the uncertainty of life. The target audience consisted of 30 individuals, including the general public and students interested in Greek mythology, art, and animated storytelling.            The results of the study revealed the following: 1) The content quality assessment by content experts resulted in an overall mean of 4.52 and a standard deviation (S.D. = 0.75), indicating that the content quality was at a highest level. 2) The media quality assessment by media experts resulted in an overall mean of 4.52 and a standard deviation (S.D. = 0.60), indicating that the media quality was at a highest level. 3) The satisfaction assessment of the target audience who watched the 2D animation resulted in a mean of 4.67 and a standard deviation (S.D. = 0.53), indicating a highest level of satisfaction.